MARKET ANALYSIS AND THE FEASIBILITY OF ESTABLISHING SMALL BUSINESSES - Abou-Moghli, Azzam Azmi; Al-Abdallah, Ghaith Mustafa (European Scientific Journal, ESJ, 2012)
This study aims to explore the nature of relation and effect between market analysis and feasibility of establishing small businesses operating in the services sector in Jordan. Four independent variables were identified to market analysis: location, demand, price and competitors. The study population consisted of (163) cases and the researchers used a close ended 42-item questionnaire, with a (83.43%) reliability coefficient, as per the Chronbach Alfa equation for collecting the primary data of the study. Furthermore, two types of analysis were employed: simple regression analysis and stepwise multiple analysis. The study made a number of conclusions, most important of which is: there is a statistically significant relationship between the location, demand, price and competitors and the feasibility of establishing small businesses.